'Our expectations were perhaps too high': disarmament, citizen activism, and the 1907 Hague Peace Conference - Hucker, Daniel (Wiley, 2018)
Historical assessments of the 1907 Hague Peace Conference, like its 1899 predecessor, are usually framed in verdicts of success or failure. Although some specialist accounts rightly portray the Hague meetings as both successful and important, most analyses of the period emphasize their shortcomings, not least the failure to prevent war in 1914. This article interrogates why the existing historiography is framed in this simplistic – and ultimately misleading – success/failure dichotomy. Focusing on hopes and aspirations regarding disarmament ahead of the 1907 Hague Conference, it contends that networks of European and American citizen activists, by doing so much to bring the conference about and legitimizing disarmament as a topic for diplomatic discussion, ensured that immediate verdicts of the conference’s work focused on the (practically non-existent) outcomes in this domain. This lack of progress overshadowed all other accomplishments of the second Hague conference and established, well before 1914, a prevailing narrative of failure.